SELECTIVE LEACHING OF LOW GRADE CALCAREOUS PHOSPHATE ROCK IN SUCCINIC ACID - Ashraf, Mohammad; Zafar, Zafar Iqbal; Ansari, Tariq Mahmood (Journal of Research (Science), 2025)
In this work, a number of experiments have been carried out to reduce the carbonate content by leaching the ground phosphate rock with dilute succinic acid solution in order to get marketable and industrially acceptable phosphate grades. By using this technique, the effect of acid concentration, reaction time, process temperature and liquid/solid ratio (v/w basis) have been studied. Depending on the reaction conditions as well as nature and size of the particles, it was found that the P2O5 percent can be raised more than 30% along with the corresponding reduction of more than 70% in the calcareous material of the sample.